Safety and adverse reactions in subcutaneous allergen immunotherapy: a review - Incorvaia, Cristoforo; Cavaliere, Carlo; Schroeder, Jan W.; Leo, Gualtiero; Nicoletta, Francesca; Barone, Alessandro; Ridolo, Erminia (Acta Biomedica Atenei Parmensis, 2023)
Background. Allergen immunotherapy (AIT) is the only treatment which acts on the causes of allergic diseases by modifying their natural history. In the eighties subcutaneous immunotherapy (SCIT) with high biological power allergen extracts caused a number of severe systemic reactions and also fatalities in the UK and the US, resulting in its limitation and in the introduction of other routes of administration. A decisive advance for SCIT safety was understanding that the major cause of mortality was injecting the allergen extract to patients with uncontrolled asthma at the time of injection.Areas covered. This awareness resulted in a significant decrease in fatalities, but not in their abolition. In 2019, an increase in SCIT-related mortality was observed, suggesting to continue the research for still unidentified factors favoring severe reactions, such as the administration of a wrong extract or of allergen doses higher than listed, unintentional intravenous administration, and missed dose reduction after protracted interruption. Moreover, in the context of the improving of the safety, the role played in tolerance-promoting by adjuvants such as CpG oligodeoxynucleotides has to be taken into account, as well as the potential preventive effect performed by the monoclonal anti-IgE antibody omalizumab against the exacerbation of severe reactions during SCIT.Conclusion. The safety of SCIT is good, but the research to improve it further must continue. In particular, the pathophysiological mechanisms related to AIT for inhalants and for Hymenoptera venom should be studied, based on the evident diversity demonstrated by the complete absence of fatal reactions to Hymenoptera venom immunotherapy from its introduction in comparison with the history of serious and fatal offenses examined in this review.